IMPLEMENTATION OF THE VALUES OF GENDER EQUALITY IN ISLAMIC RELIGIOUS EDUCATION MATERIALS IN STAI ALHIKMAH JAKARTA - Toipah Toipah; Ekawati Ekawati; Ade Pifianti; Asrori Asrori; Nurul Aida (Hikmah: Journal of Islamic Studies, 2023)
AbstractThis study aims to describe the implementation of Islamic educational values based on gender equality at STAI ALHIKMAH Jakarta. This research includes field research with research locations at STAI ALHIKMAH Jakarta. The type of research used by researchers is qualitative. The research approach used is a phenomenological approach. The results of the research show that the implementation of gender equality-based Islamic religious education values has been applied to activities on campus, especially in the lecture process, both related to integrated materials and the use of gender-responsive methods. Factors Supporting the Implementation of Gender Equality-Based Islamic Religious Education consist of internal factors and external factors. Internal factors, namely the Chair, lecturers, curriculum and special courses on gender equality values or those that are integrated. External Factors namely Parents and Environment. Solutions made by schools to the difficulties of implementing Islamic educational values based on gender equality, namely instilling Islamic educational values about gender, providing training and deepening of educational materials in Islam in understanding gender and establishing a special institution to oversee teacher behavior when discriminating against people Woman. AbstrakPenelitian ini betujuan untuk mendeskripsikan implementasi nilai-nilai pendidikan Islam berbasis kesetaraan gender di STAI ALHIKMAH Jakarta. Penelitian ini termasuk penelitian lapangan (field research) dengan lokasi penelitian di STAI ALHIKMAH Jakarta. Jenis penelitian yang digunakan peneliti adalah kualitatif. Adapun pendekatan penelitian yang dilakukan ialah pendekatan fenomenologis. Hasil peneltian menunjukkan bahwa implementasi nilai-nilai pendidikan agama Islam berbasis kesetaraan gender sudah diterapkan pada kegiatan-kegiatan di kampus terutama dalam proses perkuliahan baik yang berkaitan dengan materi yang terintegrasi ataupun penggunaan metode yang responsif gender. Faktor-faktor Pendukung Implementasi Pendidikan Agama Islam Berbasis Kesetaraan Gender terdiri dari faktor internal dan faktor eksternal. Faktor Internal yakni Ketua, dosen, kurikulum dan matakuliah khusus nilai-nilai Kesetaraan gender ataupun yang terintegrasi. Faktor Eskternal yakni Orang Tua dan Lingkungan. Solusi yang dilakukan oleh sekolah terhadap kesulitan implementasi nilai-nilai pendidikan Islam berbasis kesetaraan gender yaitu penanaman nilai-nilai pendidikan Islam tentang gender, memberikan pelatihan dan pendalaman materi pendidikan dalam Islam dalam memahami gender serta pembentukan lembaga khusus dalam mengawasi perilaku guru ketika melakukan diskriminasi terhadap kaum perempuan.